2022
DOI: 10.1111/hex.13490
|View full text |Cite
|
Sign up to set email alerts
|

‘I Don't Like Uncertainty, I Like to Know’: How and why uveal melanoma patients consent to life expectancy prognostication

Abstract: Background: Technological advances have led to cancer prognostication that is increasingly accurate but often unalterable. However, a reliable prognosis of limited life expectancy can cause psychological distress. People should carefully consider offers of prognostication, but little is known about how and why they decide on prognostication.Using uveal melanoma (UM) patients, we aimed to identify (i) how and why do people with UM decide to accept prognostication and (ii) alignment and divergence of their decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(210 reference statements)
0
2
0
Order By: Relevance
“…If proportionality of FCR is a risk factor for anxiety or depression then clinicians might focus attention on survivors with fear that is proportionate to risk. This may be particularly pertinent to population-level interventions that use population data to identify and offer tailored services to survivors based on their risk profiles (Brown et al, 2022).…”
Section: Proportiona L It Y Fcr a N D A N X I Et Y A N D Depr Essionmentioning
confidence: 99%
See 1 more Smart Citation
“…If proportionality of FCR is a risk factor for anxiety or depression then clinicians might focus attention on survivors with fear that is proportionate to risk. This may be particularly pertinent to population-level interventions that use population data to identify and offer tailored services to survivors based on their risk profiles (Brown et al, 2022).…”
Section: Proportiona L It Y Fcr a N D A N X I Et Y A N D Depr Essionmentioning
confidence: 99%
“…Patients are informed of their prognostic results, including their prognostic groups, by ocular oncology clinicians. Qualitative analyses suggest that patients understand the life-expectancy implications of their prognoses (Brown et al, 2022;Hope-Stone et al, 2015). A prospective study showed that a poor prognosis precedes moderately elevated anxiety, depression and FCR over five years (Brown et al, 2023).…”
Section: Participantsmentioning
confidence: 99%